2019
DOI: 10.3390/toxins11070402
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Flatworm Egg Plates Serve as a Possible Source of Tetrodotoxin for Pufferfish

Abstract: The pufferfish Takifugu niphobles (at present Takifugu alboplumbeus) possesses highly concentrated tetrodotoxin (TTX), an extremely potent neurotoxin that provides effective protection from predators, at least at the larval stages. However, the source of the toxin has remained unclear. Recently, DNA from the toxic flatworm Planocera multitentaculata was detected in the intestinal contents of juveniles and young of the pufferfish, suggesting that the flatworm contributes to its toxification at various stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Culturing, isolating and testing these bacterial species, in particular picocyanobacteria, for toxin production would be a logical next step in the search to identify the source of TTX in marine organisms. It has recently been shown that DNA from toxic flatworms were detected in the intestinal content of juvenile pufferfish (Okabe et al, 2019). So alternatively, it is also feasible that P. australis could source TTX from ingesting larvae, eggs, or pieces of the highly toxic sea slug P. maculata and flatworm Stylochoplana sp., which are common throughout New Zealand, Japan and Europe (Miyazawa et al, 1987;Salvitti et al, 2015;Turner et al, 2018).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Culturing, isolating and testing these bacterial species, in particular picocyanobacteria, for toxin production would be a logical next step in the search to identify the source of TTX in marine organisms. It has recently been shown that DNA from toxic flatworms were detected in the intestinal content of juvenile pufferfish (Okabe et al, 2019). So alternatively, it is also feasible that P. australis could source TTX from ingesting larvae, eggs, or pieces of the highly toxic sea slug P. maculata and flatworm Stylochoplana sp., which are common throughout New Zealand, Japan and Europe (Miyazawa et al, 1987;Salvitti et al, 2015;Turner et al, 2018).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Our previous report showed that the pufferfish T. alboplumbeus inhabiting an intertidal zone of Hayama effectively acquired the toxins by feeding on Pl. multitentaculata , and its eggs and planktonic larvae [ 19 , 44 ]. Although the biomass of Pr.…”
Section: Resultsmentioning
confidence: 99%
“…with the accumulation of tetrodotoxin in various aquatic species (Magarlamov et al, 2017;Turner et al, 2017;Leao et al, 2018). On a different line, ingestion of toxic flatworm eggs had also been suggested as the source of tetrodotoxin in pufferfish Takifugu alboplumbeus (Okabe et al, 2019). Further, since tetrodotoxin-producing strains have been isolated from skin slime and kidneys of pufferfish (Campbell et al, 2009), toxin-producing microbes could be present in other body parts of horseshoe crab instead of gut.…”
Section: Discussionmentioning
confidence: 99%